Garlic and Chitosan Improve the Microbial Quality of Hummus and Reduce Lipid Oxidation - Tareq M. Osaili; Anas A. Al-Nabulsi; Asma’ O. Taybeh; Amin N. Olaimat; Sadi Taha; Layal Karam; Mutamed Ayyash; Fayeza Hasan; Maher M. Al Dabbas; Gafar Babatunde Bamigbade; Murad Al-Holy; Ioannis N. Savvaidis; et al. (Foods)
This study investigated the antimicrobial and antioxidant effects of garlic and chitosan on hummus. Hummus was prepared by using 0.5% or 1% (w/w) chitosan, with or without 1% (w/w) garlic, and samples were stored at 4, 10, or 25 °C for 28, 21, or 7 d, respectively. The behavior of lactic acid bacteria (LAB), Pseudomonas spp., aerobic bacteria, and yeasts and molds was then investigated. Color, pH, TBARS, and rheological properties were also measured. In hummus, both with and without garlic, chitosan added at 0.5% and 1% w/w significantly (p < 0.05) decreased LAB, aerobic bacteria, yeasts, and molds, and Pseudomonas spp., at 4 °C. However, at 10 °C, adding chitosan at 1% w/w significantly reduced only aerobic bacteria (2.2 log cfu/g) and Pseudomonas spp. (1.0 log cfu/g). The pH values (regardless of treatment) decreased upon storage. The addition of garlic or chitosan did not significantly affect the lightness (L*) or yellowness (b*). However, garlic, regardless of chitosan concentration, notably reduced lipid oxidation (0.8–1.4 MDA Eq/kg of sample) and had a greater impact on the sensory properties compared to chitosan. The results of this study will encourage producers to produce hummus that has a better flavor due to garlic with enhanced microbial quality.